Efektivitas Bimbingan Kelompok Islami untuk Meningkatkan Aspirasi Karir Mahasiswa BK IKIP PGRI Madiun - Asroful Kadafi (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2016)
This study aims to improve the career aspirations of students through Islamic group guidance services. The design study is pre experimental with one type of group pre-test and post-test design. The research subjects were ten students of guidance and counseling Teacher Training College PGRI Madiun taken by purposive sampling technique. Data collection instrument used a scale of career aspirations. Analysis of data to test the effectiveness of the guidance of Islamic groups used the Wilcoxon test. The results of data analysis show a comparison z-score of -2.810 with a probability value of 0.005. Career aspirations of students before being given the Islamic guidance (pretest) showed an average score of 96.5 and after being given counseling the Islamic group (posttest) showed an average score of 131.5. It can be concluded that the Islamic group guidance services can improve students’ career aspirations of guidance and counseling Teacher Training College PGRI Madiun. The results of this study can be used as an additional reference for guidance and counseling course lecturers and counselors at universities for improving the career aspirations of students through Islamic group guidance services.